THE APPLICATION OF THE BASIC CONCEPTUAL POSITIONS AND THEORIES IN THE PROCESS OF FORMATION AND REPRODUCTION OF INTELLECTUAL CAPITAL IN MODERN PRACTICE OF ENSURING THE COMPETITIVENESS OF DOMESTIC ENGINEERING ENTERPRISES - Nahorniak, H.S. (The actual problems of regional economy development, 2019)
The article is devoted to the study of the application of the basic conceptual provisions and theories in the process of formation and reproduction of intellectual capital in the modern practice of ensuring the competitiveness of domestic machine-building enterprises. The economic content, purpose and forms of the process of development of intellectual capital in relation to human capital are revealed. The scientific approaches to the theory of intellectual capital are analyzed, on the basis of which the basic mechanisms of processes of formation and reproduction of intellectual capital of modern machine-building enterprises are theoretically substantiated. Theories of human and intellectual capital are considered, their systematization is given. Essential characteristics of retention and transformation of intellectual capital are summarized and critically analyzed in order to identify potential growth opportunities for further economic development in line with the innovation paradigm. The influence of human and knowledge on the transformation of intellectual capital is revealed. The current state is investigated and features of formation and reproduction of intellectual capital at the enterprises of machine-building complex of Ukraine are revealed. The content of the concept of “intellectual capital of the enterprise” is clarified, the author's interpretation of the main components of the intellectual capital of the enterprise, which directly contribute to the increase of competitiveness, is given. The issue of management of intellectual capital of domestic machine-building enterprises is discussed. A number of problems that directly affect the formation and reproduction of intellectual capital in machine building of Ukraine are identified. The development of intellectual capital at the enterprise level significantly increases their competitiveness, allowing to find new opportunities to gain market. Strengthening the role of intellectual resources in the development of competitiveness of the enterprise in the knowledge economy has led to a change in conditions and ways of creating value added: knowledge, skills of human resources (human capital), organizational and managerial abilities of the enterprise, its competences (structural capital) have become the main factors creating new value and actually synthesizing the emergence of intellectual capital, which can be seen as a key element of enterprise competitiveness, more precisely an element, which shapes the potential competitiveness of the enterprise. The potential of development of competitiveness of the enterprise lies in the field of formation of its intellectual capital. The higher the intellectual capital, the higher the potential competitiveness of the enterprise. Hence, more and more often, valuation of intangible assets (components of intellectual capital), such as technological assets, business strategy, corporate culture, client capital (relationship capital), reputational capital, brand equity, etc., comes to the fore when assessing the market value of the enterprise.